2011
DOI: 10.1259/dmfr/24726112
|View full text |Cite
|
Sign up to set email alerts
|

Imaging features contributing to the diagnosis of ameloblastomas and keratocystic odontogenic tumours: logistic regression analysis

Abstract: Objective: The aim of this study was to clarify the characteristic imaging features that can be used to differentiate ameloblastomas from keratocystic odontogenic tumours and to examine the significant imaging features contributing to a correct diagnosis. Methods: 60 observers (39 specialists in oral and maxillofacial radiology and 21 nonspecialists) examined CT and/or panoramic images of 10 ameloblastomas and 10 keratocystic odontogenic tumours shown on a webpage and made diagnoses. Their correct answer ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 16 publications
(37 reference statements)
2
38
0
5
Order By: Relevance
“…According to literature odontogenic keratocysts have lower CT density with higher heterogeneity than Ameloblastomas. 5 One of the studies showed a significant difference regarding bony expansion, impacted teeth and high-density areas between the two. 5 According to this study, the presence of highdensity areas is the most useful feature in the differential diagnosis of ameloblastomas and keratocystic odontogenic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…According to literature odontogenic keratocysts have lower CT density with higher heterogeneity than Ameloblastomas. 5 One of the studies showed a significant difference regarding bony expansion, impacted teeth and high-density areas between the two. 5 According to this study, the presence of highdensity areas is the most useful feature in the differential diagnosis of ameloblastomas and keratocystic odontogenic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In reference to an article by Ariji et al, 1 we would like to thank the authors for an informative study. This article was enlightening owing to the paucity of studies conducted regarding this subject.…”
mentioning
confidence: 99%
“…Com a enucleação raramente ocorre recorrência (SCHOLL et al, 1999;FREITAS et al, 2006;BUYUKKURT;OMEZLI;MILOGLU, 2010;MACANOVIC, 2010 odontogênico queratocístico e o cisto dentígero podem apresentar aspecto radiográfico indistinguível: uma lesão radiolúcida unilocular, bem definida e corticalizada, frequentemente associada à coroa de um dente impactado ou não irrompido, como também podem apresentar grandes proporções e aspecto multilocular com bordas festonadas. O que torna difícil a hipótese de diagnóstico baseada somente nos aspectos radiográficos (WEBER, 1993;SCHOLL et al, 1999;CHAPELLE et al, 2004;DUNFEE et al, 2006;FREITAS et al, 2006;BOEDDINGHAUS;WHYTE, 2008;MCCREA, 2009;ARIJI et al, 2011;MORGAN, 2011;TITINCHI;NORTJE, 2012;SANSARE et al, 2013 A avaliação foi realizada com o uso de um negatoscópio, com auxílio de uma lupa de 60mm de diâmetro e aumento de 3x, em um ambiente com iluminação adequada. Nenhum dado clínico foi informado.…”
Section: Cisto Dentígerounclassified
“…O ameloblastoma e o tumor odontogênico queratocístico são os mais frequentes tumores odontogênicos e o cisto dentígero é o mais frequente cisto odontogênico de desenvolvimento e o segundo cisto odontogênico mais comum. A imagem radiográfica pode ser muito semelhante e variar desde uma lesão radiolúcida, unilocular, de borda esclerótica bem definida, a uma lesão radiolúcida extensa, multilocular e de bordas festonadas; frequentemente associadas à coroa de um dente impactado ou não irrompido (WEBER, 1993;SCHOLL et al, 1999;CHAPELLE et al, 2004;DUNFEE et al, 2006;FREITAS et al, 2006;BOEDDINGHAUS;WHYTE, 2008;MCCREA, 2009;ARIJI et al, 2011;MORGAN, 2011;TITINCHI;NORTJE, 2012;SANSARE et al, 2013).…”
Section: Sobre a Concepção Do Trabalhounclassified
See 1 more Smart Citation